Pilot scale extraction of proteolytic enzyme bromelain from pineapple (ananas comosus) - Loh, Melissa Pei Shian; Syamsul Baharil, Nur Aishah; Ting, Lee Yu; M., Taher; Abdul Majid, Fadzilah Adibah (2005)
Bromelain is a complex of proteolytic enzymes obtained from pineapple (Ananas comosus) fruits and stem. These proteolytic enzymes are tools that promise an impressive number of medical and therapeutic uses, particularly as anti-inflammatory agents, dietary supplements and analgesics. The purpose of this study was to develop a pilot scale bromelain extraction process. The bromelain extraction method using pineapple fruit core in this study has yielded a total protein content of 9.33 mg/ml with the proteolytic activity of 1400 GDU/ml. An increase in homogenization cycle to increase enzyme yield has proven to be successful. Triple-loop homogenization has shown three times higher proteolytic activity than non-homogenized sample.